2015
DOI: 10.1055/s-0034-1378723
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition of Malonates to Enones Catalyzed by an α-d-Glucopyranoside-Based Crown Ether

Abstract: The chiral monoaza-15-crown-5 lariat ether annelated to methyl-4,6-O-benzylidene-α-D-glucopyranoside has been applied as a phase-transfer catalyst in several Michael addition reactions under mild conditions affording the adducts with good to excellent enantioselectivities. In the addition of α-substituted diethyl malonates to trans-chalcones, the substituents of the reactants had a significant impact on the yield and enantioselectivity. Among the reactions of substituted diethyl malonates, that of diethyl-2-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 5 publications
1
32
0
Order By: Relevance
“…It was noticed in 1 of our previous studies that the 4-methyl substitution increased significantly the enantioselectivity of this reaction under discussion using carbohydrate-based crown ethers. 31 To our surprise, depending on the substituent of the catalysts, much better results were achieved in this reaction ( Table 3, entries 10-15). Cyclopropane derivative 17b was obtained in good yields (81-90%) and with uniformly excellent enantiomeric excesses (99% ee, 96% ee, 98% ee, and 99% ee, respectively) in the presence of lariat ethers having hydroxypropyl side arm (2a, 2c, 2e, and 2f).…”
Section: Application Of the Macrocycles In Asymmetric Synthesesmentioning
confidence: 84%
“…It was noticed in 1 of our previous studies that the 4-methyl substitution increased significantly the enantioselectivity of this reaction under discussion using carbohydrate-based crown ethers. 31 To our surprise, depending on the substituent of the catalysts, much better results were achieved in this reaction ( Table 3, entries 10-15). Cyclopropane derivative 17b was obtained in good yields (81-90%) and with uniformly excellent enantiomeric excesses (99% ee, 96% ee, 98% ee, and 99% ee, respectively) in the presence of lariat ethers having hydroxypropyl side arm (2a, 2c, 2e, and 2f).…”
Section: Application Of the Macrocycles In Asymmetric Synthesesmentioning
confidence: 84%
“…A few preliminary results have already been published. 21 Besides that, we used enones containing naphthalene, thiophene and pyridine rings as the aryl substituents (Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…61 Previously, we found that a glucopyranoside-based macrocycle generated asymmetric induction in the reaction of chalcone 9a with diethyl acetoxymalonate (15). 46 It was a challenge for us to test the threitol-based lariat ethers in this reaction. In our experiments, the conjugate addition of diethylmalonate (15) to trans-chalcones 9a-f was carried in a mixture of THF-ether as the solvent in the presence of Na 2 CO 3 (used in 2-fold excess) employing 15 mol% of the crown ether at room temperature to afford the chiral Michael adducts 16a-f.…”
Section: Methodsmentioning
confidence: 99%
“…The organic layer was washed with cold 10% HCl (3 x 10 ml) and then with water (10 ml), dried (Na 2 CO 3 and Na 2 SO 4 ), and concentrated. The crude product was purified by preparative TLC using silica gel and hexane-EtOAc 2.6 | General procedure for asymmetric model reactions using malonates [46][47][48] Unsaturated compound (1 mmol), substituted malonate (1.5 mmol) and the crown ether (0.15 mmol) were dissolved in a mixture of anhydrous THF (0.6 ml) and Et 2 O (2.4 ml) and dry Na 2 CO 3 (0.22 g, 2 mmol) was added. The reaction mixture was stirred at RT.…”
Section: General Procedures For Preparation Of Threitol-based Crown mentioning
confidence: 99%